Karateristik Distribusi Frekuensi Ibu Pascamelahirkan dengan Kejadian Postpartum Blues Bandar Lampung 2019 - Fonda Octarianingsih; Festy Ladyani; Woro Pramesti; Nahlah Fathin Nabilah (Puslitbang Sinergis Asa Professional, 2020)
Postpartum blues is a mood felt by women after childbirth, which lasted for 3-6 days in the first 14 days postpartum, which is related to the baby's feelings (Mansur, 2009: 156). Objective: This study aimed to determine the distribution frequency of postpartum mothers with postpartum blues case in Puskesmas Kemiling and midwife clinic in sub-district of Kemiling, Bandar Lampung Midwife Sub-district Practices in Bandar Lampung. This study also aimed to know the characteristics of postpartum maternal frequency distribution with postpartum blues incidents in the Puskesmas Inpatient Center and Midwife Practices in Bandar Lampung sub-district. The type of research used in this study was quantitative descriptive. The sample used at least 30 postpartum mothers in Puskesmas Kemiling and midwife clinics in Kemiling. The results of research conducted in Puskesmas Kemiling and midwife clinics Kemiling Bandar Lampung for the frequency distribution of the postpartum blues cases, it is found that mothers who experienced postpartum blues were about 6 respondents (14,6%) and mothers who did not experience postpartum blues were about 35 respondents (85,4%). It is known that from 41 postpartum mothers, most of them did not experience postpartum blues. The postpartum blues cases in Puskesmas Kemiling and midwife clinics Kemiling were at 14,6%. Most of respondents were aged 21-35 years old, multiparous, vaginal, low education, work, income above regional minimum wage.